Analysis of Students’ Perception on Quality of Management Education in Kathmandu - Tripathee, Aaratee (Journal of Business and Social Sciences Research, 2018)
This paper examines the students’ perception on quality of MBA program and the relationship between the perceived quality and satisfaction of the students with the MBA program. For this study 250 respondents, 50 each from five universities, pursuing MBA degree were taken as sample and surveyed through structured questionnaire in the year 2016. Five variables are taken as the major quality indicators: quality of curriculum, faculty, employability, infrastructure, and reputation. For data analysis, descriptive, analytical and inferential techniques have been employed. The perceptions of the students are analyzed against the five quality dimensions where significant relationship is seen between the satisfaction of the students and faculty, employability, infrastructure and reputation. The study observed that a good brand name is often associated with quality and it is likely to think that good reputation is bound with good curriculum, faculty, employability and infrastructure. Hence, educational institutions should work on building good rapport in the market as it exerts strong effect on the overall satisfaction of students. This can be promoted by highlighting graduate employability and by indicating the career success and development of the graduates and alumni. The finding also revealed that the factors do affect the students’ perception and among the selected five quality dimensions ‘reputation’ is seen as the most influential factor in forming students perception and ‘curriculum’ is seen as the least influential factor as there is not much difference in curriculum provided by different universities. Journal of Business and Social Sciences Research, Vol. 2, No. 1 & 2, pp. 15-26